CdSe quantum dot organic solar cells with improved photovoltaic performance. (13th January 2021) - Yang, Xi-Kai; Qiao, Jia-Wei; Chen, Zhi-Hao; Wen, Zhen-Chuan; Yin, Hang; Hao, Xiao-Tao
Abstract: We adopt inorganic semiconducting CdSe quantum dots (QDs) as a third component in the PTB7-Th:PC71 BM-based organic solar cells due to their advantages of strong absorbance, high conductivity, and good solution processability. With the blending of low-dosage CdSe QDs, the short-circuit current density ( J sc ) and power conversion efficiencies can be improved by 13% and 11%, respectively, in the ternary device. Compared with the control device, CdSe QDs can effectively modulate the charge dynamics and lead to enhanced fluorescence external quantum efficiency. Moreover, effective Förster resonance energy transfer and fast charge transfer can be observed in the CdSe QD-based bulk-heterojunction (BHJ) films, and therefore improve the overall performance of the organic photovoltaic devices. This work provides an effective method by adopting CdSe QDs to fabricate high-performance PTB7-Th:PC71 BM BHJ solar cells.